Prevalence and prognostic impact of left ventricular systolic dysfunction or pulmonary congestion after acute myocardial infarction. (2nd February 2023) - Hamilton, Eleonora; Desta, Liyew; Lundberg, Anna; Alfredsson, Joakim; Christersson, Christina; Erlinge, David; Kellerth, Thomas; Lindmark, Krister; Omerovic, Elmir; Reitan, Christian; Jernberg, Tomas
Abstract: Aims: The aim was to describe the prevalence, characteristics, and outcome of patients with acute myocardial infarction (MI) developing left ventricular (LV) systolic dysfunction or pulmonary congestion by applying different criteria to define the population. Methods and results: In patients with MI included in the Swedish web‐system for enhancement and development of evidence‐based care in heart disease (SWEDEHEART) registry, four different sets of criteria were applied, creating four not mutually exclusive subsets of patients: patients with MI and ejection fraction (EF) < 50% and/or pulmonary congestion (subset 1); EF < 40% and/or pulmonary congestion (subset 2); EF < 40% and/or pulmonary congestion and at least one high‐risk feature (subset 3, PARADISE‐MI like); and EF < 50% and no diabetes mellitus (subset 4, DAPA‐MI like). Subsets 1, 2, 3, and 4 constituted 31.6%, 15.0%, 12.8%, and 22.8% of all patients with MI ( n  = 87 177), respectively. The age and prevalence of different co‐morbidities varied between subsets. For median age, 70 to 77, for diabetes mellitus, 22 to 33%; for chronic kidney disease, 22 to 38%, for prior MI, 17 to 21%, for atrial fibrillation, 7 to 14%, and for ST‐elevations, 38 to 50%. The cumulative incidence of death or heart failure hospitalization at 3 years was 17.4% (95% CI: 17.1–17.7%) in all MIs; 26.9% (26.3–27.4%) in subset 1; 37.6% (36.7–38.5%) in subset 2; 41.8% (40.7–42.8%) in subset 3; and 22.6% (22.0–23.2%) in subset 4. Conclusions: Depending on the definition, LV systolic dysfunction or pulmonary congestion is present in 13–32% of all patients with MI and is associated with a two to three times higher risk of subsequent death or HF admission. There is a need to optimize management and improve outcomes for this high‐risk population.